Improving the chemical quality of sandy-textured soil and shallot (Allium cepa L.) yields using biochar and clay - Raesa Sakinah Siregar; Khusrizal; Yusra; Nasruddin (Universitas Lancang Kuning, 2023)
Sandy soils are known as low-fertility soils due to the soil's limited physical, chemical, and biological properties. Rice husk biochar and clay soil are organic and inorganic materials that can improve soil quality levels. This study aims to improve the chemical quality of sandy soil and shallot crop yields using rice husk biochar and clay. The study was arranged using a factorial randomized block design, with rice husk biochar as the first factor and soil clay as the second factor. Rice husk biochar consisted of four levels, and three levels for clay. The chemical properties of the soil observed included pH, organic-C, cation exchange capacity (CEC), available-P (av-P), and exchangeable-K (K-ex). The yield of shallots was measured as the number of tubers and each tuber's wet and dry weight. The result showed that soil pH tended to vary and decreased from 6.9 in the initial soil to 6.4. Organic-C content increased from 0.11% initial soil to 0.31% and CEC from 6.80 cmolc/kg initial soil to 19.60 cmolc/kg. Av-P and K-ex levels varied and increased, where av-P increased from 97.65 mg/kg of the initial soil to 105.15 mg/kg, and K-ex levels increased from 0.20 cmolc/kg of the initial soil to 0.65 cmolc/kg. The combination of rice husk biochar and clay had no significant effect on the shallot yield. Rice husk biochar and clay could improve the chemical quality of sandy-textured soil. Both rice husk biochar and clay independently increase shallot yields.